2022
DOI: 10.1007/s40279-022-01791-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance Adaptations to Intensified Training in Top-Level Football

Abstract: Because physical demands are surging in football (soccer, USA), clubs are more and more seeking players who have a high capacity to perform repeated intense exercise. High-intensity interval training (HIIT), comprising exercise performed at intensities near or exceeding the capacity of aerobic energy systems, effectively enhances the physical conditioning of players. But given that HIIT imposes high loads, it increases the risk of overload-associated match performance decline and injury. This makes some coache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 132 publications
1
16
0
1
Order By: Relevance
“…Anaerobic endurance is continuous with the level of fatigue with a good anaerobic level, it influences the small risk of injury due to fatigue, which results in a decrease in an athlete's performance Güler et al (2020); Lopes et al (2019), in line with a significant reduction in the fatigue index of the experimental group who received rotation play training with HIIT Protocol. High-intensity interval training (HIIT) is an effective exercise regimen for improving several physiological parameters important for performance, including cardiometabolic function, oxygen uptake kinetics, strength and anaerobic capacity, ion transport capacity, and muscle fatigue resistance (Hostrup & Bangsbo, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic endurance is continuous with the level of fatigue with a good anaerobic level, it influences the small risk of injury due to fatigue, which results in a decrease in an athlete's performance Güler et al (2020); Lopes et al (2019), in line with a significant reduction in the fatigue index of the experimental group who received rotation play training with HIIT Protocol. High-intensity interval training (HIIT) is an effective exercise regimen for improving several physiological parameters important for performance, including cardiometabolic function, oxygen uptake kinetics, strength and anaerobic capacity, ion transport capacity, and muscle fatigue resistance (Hostrup & Bangsbo, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…One solution that can be adopted to overcome the problems faced in developing physical, technical, tactical and mental components is to apply the Speed Endurance Soccer Training (SEST) model. This exercise adopts the Long Interval Speed Endurance Training Maintenance (SET-M) theory with an intensity of 50-80%, 15-90 seconds duration, ratio 1:1-1:3, and repetitions 6-12 (Hostrup & Bangsbo, 2023). This approach combines elements of high-intensity speed training with tactical elements in matches, in line with the research of M. Oliva-Lozano et al (2023), who found that repeated sprinting abilities are very much needed in soccer.…”
Section: Introductionmentioning
confidence: 89%
“…On FI.RE. framework, a five-stage football functional rehabilitation framework,20–43 engages in therapeutic exercises that interact with football skills. This framework addresses aspects including function and power restoration, cardiorespiratory endurance, cognitive ability and neuromuscular skills specifically related to football scenarios (tables 1 and 2).…”
Section: Methodsmentioning
confidence: 99%